Stimulation-Induced Artifact Removal of the Local Field Potential Through Hardware Design: Toward the Implantable Closed-Loop Deep Brain Stimulation - Yi-Hui Wu; Hsiao-Chun Lin; Chi-Wei Huang; Chung-Yu Wu; Ming-Dou Ker (IEEE Access)
Deep brain stimulation is a standard neurosurgery to treat advanced Parkinson’s disease patients. An innovative technology known as closed-loop deep brain stimulation is under development. This technology aims to identify abnormal biomarker signals within the brain, and create novel systems featuring sophisticated hardware configurations to generate improved therapeutic approaches and more favorable outcomes. The primary challenge faced in advancing closed-loop deep brain stimulation is managing artifacts induced by electrical stimulation within the signal detection module. A notable circuit design challenge involves continuously monitoring local field potential alterations during electrical stimulation. The artifacts arising from the stimulation can be categorized into common-mode artifact voltage and differential-mode artifact voltage. Within this article, a comprehensive review encompasses recent methodologies designed to mitigate common-mode artifact voltage and differential-mode artifact voltage in local field potential through hardware-centric techniques, including filtering, template removal, blanking, and selective sampling. The inherent strengths and limitations of these strategies are compared and discussed. This article allows engineers to recognize appropriate artifact removal techniques to achieve an implantable closed-loop deep brain stimulation system. To this end, a more intelligent and more precise system could be developed for the treatment of Parkinson’s disease and other neurological disorders.